Goden en idolen. - Baudelaire, Charles; Debruyn, Mimi; Smith, Patti; van Ostaijen, Paul (Turnhout : de Warande, 1983)
Appel, Karel ; van den Berghe, Frits ; Boezem, Marinus ; Broodthaers, Marcel ; Delville, Jean ; de Dominicis, Gino ; Dotremont, Christian ; Gentils, Vic ; Joostens, Paul ; Khnopff, Fernand ; Kiefer, Anselm ; Kounellis, Jannis ; Luyten, Mark ; Paik, Nam June ; Panamarenko ; Paolini, Giulio ; Pauwels, Achiel ; Redon, Odilon ; Saura, Antonio ; Vaerten, Jan ; Vermeiren, Didier ; Vertessen, Liliane ; Warhol, Andy ; de Wouwer, R. Van
Nederlands
Goden en idolen, De Warande, Turnhout, van 12 maart tot 10 april 1983
kunstcatalogus